Evaluation Of The Transfer Of Road Safety Knowledge From The Motor Transport Industry To Young Drivers - Chai, Jefferson Chi Khoon (2002)
This report links knowledge management concepts to the field of road safety, in particular the area of driver education programmes. The results of the experiment were tabulated and discussed. The present study indicated that the use of interactive presentation of expert knowledge had the most effectual changes in the young drivers' self-reported driving behaviours. Moreover , the present study indicated that males and females responded equally to the different combination of knowledge content and presentation style. Further analysis revealed that significant changes in the self-reported driving behaviour in traffic of either males or females alone were determined by the combined effects of the presentation content and presentation style. Nonetheless, the results of the present study warrants further investigation.